2014
DOI: 10.15298/arthsel.23.4.02
|View full text |Cite
|
Sign up to set email alerts
|

A review of the anthropochore millipede fauna of Asian Russia, with new records from the Altai Province, Siberia (Diplopoda)

Abstract: The anthropochore millipede fauna of Asian Russia is reviewed, based on the available literature records, as well as new samples from the Altai Province and only partly published, freshly revised material [Nefediev, Nefedieva, 2006, 2011]. The julid genus Brachyiulus Berlese, 1884, as well as B. jawlowskii Lohmander, 1928, are new to the millipede faunas of Asian Russia and Kazakhstan. The polydesmid genus Brachydesmus Heller, 1858 and B. superus Latzel, 1884 are reported from Asian Russia for the first time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 1 publication
0
16
0
2
Order By: Relevance
“…Це новий вид для фауни азіатської частини Росії. Нині його зареєстровано в семи антропогенних біотопах у містах Барнаул і Бійськ, а також на відкритому робочо-му майданчику в Первомайському районі Алтайського краю (Nefediev et al, 2014). У Ставропольському краї B. jawlowskii не знайдений у природному середовищі, тому, ймовірно, тут він -чисто синантропна форма (Zuev, 2014).…”
Section: вступunclassified
See 1 more Smart Citation
“…Це новий вид для фауни азіатської частини Росії. Нині його зареєстровано в семи антропогенних біотопах у містах Барнаул і Бійськ, а також на відкритому робочо-му майданчику в Первомайському районі Алтайського краю (Nefediev et al, 2014). У Ставропольському краї B. jawlowskii не знайдений у природному середовищі, тому, ймовірно, тут він -чисто синантропна форма (Zuev, 2014).…”
Section: вступunclassified
“…B. jawlowskii заселяє всі досліджені біотопи в межах арени р. Дніпро -вид екологічно пластичний. За даними багатьох дослідників (Enghoff, 2006;Wytwer et al, 2009;Nefediev et al, 2014), останнім часом спостерігається тенденція до розширення ареалу цього виду. Загальний механізм подолання кліматичних рубежів ґрунтовими тваринами -принцип зональної зміни стацій (Bey-Bienko, 1930).…”
Section: результати та їх обговоренняunclassified
“…Despite the recent increased interest in the myriapod fauna of southwestern Siberia (Mikhaljova et al 2007, 2008, 2014, 2015, Mikhaljova 2009, 2013, 2016, 2017, Nefediev et al 2013, 2014a, b, c, 2016a, b, c, 2017a, b, Nefedieva et al 2014, 2015, Nefediev 2016), the biodiversity and ecological characteristics of myriapods in the study area of the lowland Altais, a transition zone from the plains of the southwestern Siberia to the mountains of southern Siberia have not been studied to date.…”
Section: Introductionmentioning
confidence: 99%
“…Koch, 1847, has been recorded by Mikhaljova and Nefediev [2003] in the University Grove at the Tomsk State University, Tomsk City, Tomsk Area, southwestern Siberia. The species could have reached the grove from the nearby hothouses of the Siberian Botanical Garden [Nefediev et al, 2014]. It has also been introduced to the Baktin Cemetery in the suburbs of the city of Tomsk, presumably with flower seedlings [Nefediev, Nefedieva, 2011], as well as to some other open man-made grounds [Nefediev et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…The species could have reached the grove from the nearby hothouses of the Siberian Botanical Garden [Nefediev et al, 2014]. It has also been introduced to the Baktin Cemetery in the suburbs of the city of Tomsk, presumably with flower seedlings [Nefediev, Nefedieva, 2011], as well as to some other open man-made grounds [Nefediev et al, 2014]. The second invasive polydesmidan species from the study area, Brachydesmus superus Latzel, 1884, has been reported very recently from hothouses of the South Siberian Botanical Garden and from open hand-made grounds in the environs of the city of Barnaul, Altai Province, southwestern Siberia [Nefediev et al, 2014].…”
Section: Introductionmentioning
confidence: 99%